2011
DOI: 10.1098/rsbl.2011.0025
|View full text |Cite
|
Sign up to set email alerts
|

Temporal changes in greenspace in a highly urbanized region

Abstract: The majority of the world's population now lives in towns and cities, and urban areas are expanding faster than any other land-use type. In response to this phenomenon, two opposing arguments have emerged: whether cities should ‘sprawl’ into the wider countryside, or ‘densify’ through the development of existing urban greenspace. However, these greenspaces are increasingly recognized as being central to the amelioration of urban living conditions, supporting biodiversity conservation and ecosystem service prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
100
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 171 publications
(101 citation statements)
references
References 10 publications
1
100
0
Order By: Relevance
“…During the process of urban sprawl, land in the wider countryside is gradually occupied, and new green space is constructed artificially (e.g. Antrop, 2000;Swenson and Franklin, 2000;Dallimer et al, 2011). Where and how urban green space is distributed is commonly controlled entirely by humans, which means that socio-economic factors significantly influence green space coverage in built-up areas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the process of urban sprawl, land in the wider countryside is gradually occupied, and new green space is constructed artificially (e.g. Antrop, 2000;Swenson and Franklin, 2000;Dallimer et al, 2011). Where and how urban green space is distributed is commonly controlled entirely by humans, which means that socio-economic factors significantly influence green space coverage in built-up areas.…”
Section: Discussionmentioning
confidence: 99%
“…In response to the fast-developing urban expansion, two opposing arguments have emerged: whether cities should be allowed to 'sprawl' into the wider countryside, or 'densify' through the development of existing urban green space (Dallimer et al, 2011). By 'sprawl' into the wider countryside, it is feared that the urban sprawl leads to settlement patterns which are environmentally inefficient and have negative impacts on the surrounding countryside (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have showed that enhanced vegetation index (EVI) is more appropriate for monitoring vegetation dynamics in urban areas usually covered by sparse vegetation than the NDVI [39][40][41]. In this study, MODIS EVI data (MOD13A2, Terra satellite, 1 km spatial resolution, 16 day composite) from 2001 to 2016 was used to extract the vegetation information.…”
Section: Modis Lst and Evi Datamentioning
confidence: 99%
“…The density of urban areas is also increasing in many UK cities often at the expense of green spaces (Dallimer et al, 2011). Urban and garden ponds are likely to play an increasingly important role in supporting and contributing to urban biodiversity and mitigating against urban biodiversity loss (Colding et al, 2009;Hassall and Anderson, 2015).…”
Section: Urban Pondsmentioning
confidence: 99%
“…Compact, high density commercial and residential spaces are being built as urban population growth continues to increase; however this urban 'densification' is at the expense of much of the urban green space that remains in towns and cities (Dallimer et al, 2011). Traditionally, ecological conservation has relied heavily on the designation of areas protected from development or modification by legislation and policy (Mcdonald et al, 2008).…”
Section: Introductionmentioning
confidence: 99%